Anti-inflammatory activity of the lipid extract of Mytilus crassitesta - YUAN Gao-feng; YAO Ting; LI Jiong; ZHANG Zhi-guo; LI Duo (浙江大学学报. 农业与生命科学版, 2007)
The anti-inflammatory activity of the Mytilus crassitesta lipid extract was investigated by using tissue hyperplasia assay and adjuvant arthritis model in rats. The results showed that the Mytilus crassitesta lipid extract had significant anti-inflammatory activity. The tissue hyperplasia was significantly inhibited and primary and secondary symptoms of adjuvant-induced arthritis were significantly alleviated in Mytilus crassitesta lipid extract treatment group compared with vegetable oil group. The anti-inflammatory activity of the Mytilus crassitesta lipid extract was comparative with Lyprinol, a lipid extract of New Zealand green-lipped mussel (Perna canaliculus). Present study provides theoretical basis for exploitation of Mytilus crassitesta as functional food with anti-inflammatory activity or effective and safe anti-inflammatory drugs.